(untitled) (Experimental biology, 2015)
A high level of actinomycetes presence was detected in the rhizosphere of sandy soils and sand plants in arid areas of South Kazakhstan. It is established that in a radical zone of plants the quantitative contents of actinomycetes is 2,5- 5,5 times more, than in the soil. The qualitative composition of actinomycetes in samples of sandy soils and plant root zone of sandy soils is quite diverse.